توظيف التقنيات الحديثة والأنظمة الخبيرة في مكافحة الجرائم الدولية ضمن الأطر القانونية للمحكمة الجنائية الدولية: دراسة في أحكام القانون الإماراتي والدولي: Employing Modern Technologies and Expert Systems in Combating International Crimes within the Legal Frameworks of the International Criminal Court: A Study of the Provisions of UAE and International Law - Almarzooqi, Faisal Ali Ebrahim; Musa, Abdul Samat; Ismail, Abdulmanan (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2023)
ملخص البحث تهدف الدراسة إلى معرفة النظم الخبيرة ولتقنيات الحديث في مكافحة الجرائم الدولية كالإرهاب الدولي وأثره على الفكر المعاصر ومواجهته على المستوى الداخلي والخارجي الدولي. من خلال معرفة هذه النظم الخبيرة والأطر القانونية التي تحدد العلاقة بقانون العقوبات الإماراتي واختصاصات المحكمة الجنائية الدولية لمكافحة هذه الجرائم الخطيرة، وردعها وفي ضوء ذلك، وإعادة النظر في اختصاص المحكمة الجنائية الدولية بما يتناسب مع الجرائم الدولية والتي تنشئ بشكل مستمر وبأوجه مختلفة وبيان علاقة تكاملية بين الدول الأعضاء في القضاء الوطني والاختصاص القضائي لمحكمة الجنايات الدولية وكيف تؤثر النظم الخبيرة والتقنيات الحديثة عليها. واعتمد البحث على المنهج الوصفي التحليلي الاستقرائي بهدف الوصول الى نتائج موضوعيه تحقق الهدف من هذه الدراسة، وتوصل البحث الى مجموعه من النتائج أهمها تكاملية العلاقة بين المحكمة الجنائية الدولية والمحاكم الوطنية بما يساعد على تطبيق القوانين النافذة في مكافحة الجرائم الدولية عبر النظم الخبير والتقنيات الحديثة وخرج البحث بتوصيات اهمها وجود المحكمة الجنائية الدولية ذات استقلاليه كآلية ضرورية لضمان احترام مبادئ القانون الدولي وحمايـة حقـوق الإنسـان وإنصاف الضحايا، في ظل عدم وجود، آلية أخرى دائمة وفعالة لمسألة الأشخاص الذين ينتهكون قواعد القانون الدولي ويقترفون أبشع الجرائم في حـق الإنسـانية. وأيضا دعوة لكافة الدول وخاصة الدول العربية إلى إجراء تعديلات في تشريعاتها الوطنية مع المعايير الدولية وتطبيق النظم الخبيرة والتقنيات الحديثة فيها. ABSTRACT The study aims to know the expert systems and modern techniques in combating international crimes such as international terrorism and its impact on contemporary thought and confronting it at the internal and external international levels. Through knowledge of these expert systems and legal frameworks that determine the relationship with the UAE Penal Code and the jurisdiction of the International Criminal Court to combat these serious crimes, deter them, and in light of that, reconsider the jurisdiction of the International Criminal Court in proportion to international crimes that are created continuously and in different aspects, and demonstrate a complementary relationship between Member states in the national judiciary and the jurisdiction of the International Criminal Court and how expert systems and modern technologies affect them. The research relied on the descriptive analytical inductive method in order to reach objective results that achieve the goal of this study. The research reached a set of results, the most important of which is the complementary relationship between the International Criminal Court and national courts, which helps implement the applicable laws in combating international crimes through expert systems and modern technologies. The research came up with recommendations, the most important of which is the existence of an independent International Criminal Court as a necessary mechanism to ensure respect for the principles of international law, protection of human rights, and justice for victims, in the absence of another permanent and effective mechanism for the issue of people who violate the rules of international law and commit the most heinous crimes against humanity. It is also a call to all countries, especially Arab countries, to make amendments to their national legislation in line with international standards and to apply expert systems and modern technologies to them.